Efeitos da auriculoacupuntura na promoção do conforto de puérperas - Aquino, Caroline Batista de Queiroz (2021)
This study aimed to evaluate the effect of auriculoacupuncture in promoting comfort in postpartum women. This is an experimental study, of the randomized controlled clinical trial type, carried out in the city of Fortaleza, in the sectors of the Neonatal Intensive Care Unit and Kangaroo Unit of the Maternity School Assis Chateaubriand, developed with postpartum women who accompanied their hospitalized babies, from February to July 2019. Participants were randomly allocated into two groups, the intervention group, postpartum women who received auriculoacupuncture sessions with semi-permanent needles at the Shemen, kidney, SNV, anxiety, heart, lung and neurasthenia points and routine care of the service, and the control group, composed of postpartum women who received placebo acupuncture, who had needles inserted in regions of the ear that had no effects, and routine care provided by the service. The treatment consisted of up to three sessions, with intervals of three days. This study used the recommendations from the Standards for Reporting Interventions in Clinical Trials of Acupuncture checklist items. The instrument used to investigate the sociodemographic, clinical and obstetric profile, the general comfort scale – Brazilian version, was used to assess the comfort of postpartum women. Data were entered into Microsoft Excel for Windows and analyzed using the R statistical software. The Shapiro-Wilk test was used to analyze the normality of continuous variables. The z test of proportions was used to compare categorical variables between groups. The T-test was used for comparative analysis of the mean scores of the total scale and domains. The Mann-Whitney test was used to compare continuous variables (Pain Scale, Beck Anxiety and IDATE). The Wilcoxon test was used to compare paired measures between sessions. For purposes of statistical significance, values of p<0.05 were adopted. Regarding the results, the comparison of sociodemographic, clinical and obstetric characteristics evaluated allowed us to infer that the groups are statistically similar and, therefore, comparable (p>0.05), except for the pregnancy variable. When comparing the assessment of the general score of the General Comfort Questionnaire of the groups, it was observed that there was no statistical significance, which denotes that the intervention performed, the auriculoacupuncture, did not manage to increase the level of perceived comfort, but had an increase in the averages in the total score and in the Sociocultural domain after the first session, in the Physical and Environmental domains in the baseline and first session. Assessing each comfort domain, statistical significance was observed in the physical domain in the control group, which indicates an increase in the comfort level in this group and in the sociocultural domain in both the intervention group and the control group, causing an increase in the comfort level in these groups. In the evaluation of the variables that influenced comfort, income above 2 minimum wages, having an occupation outside the home environment and having an adequate body mass index influenced the improvement in comfort in the control group. In this context, it is noteworthy that the intervention was not effective in the intervention group, but it is necessary to understand the various nuances that the phenomenon of comfort has, along with the moment experienced by this woman in the process of hospitalization of their babies. In this context, care for women who experience the puerperium should aim to offer strategies with actions aimed at overcoming difficulties and preparing women to perform the care inherent in this period.